Occult pneumococcal bacteraemia and febrile convulsions. Issue 6360 (15th January 1983) - McIntyre, P; Kennedy, R; Harris, F
Abstract : Over two years 29 children had bacteraemia due to Streptococcus pneumoniae at this hospital. In 15 previously healthy children the site of infection could not be identified, and in most of them, bacteraemia was not suspected clinically. All 15 had high total white cell (greater than or equal to 17 x 10(9)/1) and neutrophil (greater than or equal to 11 x 10(9)/1) counts. Twelve children were under 4 years of age, and of these, 10 had been admitted because of a simple febrile convulsion and one had a prolonged febrile convulsion. Occult pneumococcal bacteraemia has been reported in the USA for more than 10 years, but no series has been reported from the United Kingdom. Occult pneumococcal bacteraemia may be an important cause of febrile convulsions. Persisting bacteraemia and the development of focal infections, including pneumococcal meningitis, have been reported. Meningitis did not occur after occult bacteraemia in our patients. Studies to date have been retrospective, and thus the true incidence of the complications and the best treatment are not clear. A prospective study of children with febrile convulsions could provide answers.